Learning Management in Classroom Organization SMA IT Permata Hati Tebing Tinggi City - Eka Lestari; Nadhilah Ajrina; Khoirun Isnawan; Ilham Muhammad Fajar (Edumaspul: Jurnal Pendidikan, 2022)
Learning management has a very important role in the success of the teaching and learning process in schools. Good management in a school is very influential for the smooth and successful learning. Class organization means a group of people whose scope consists only of the class itself with the driving coordinator being the homeroom teacher. The purpose of this research is to find out the management of learning in the class organization of SMA IT Permata Hati Tebing Tinggi City. In addition, this study also aims to find out directly about the problems faced by teachers who teach at the SMA IT Permata Hati High School in Tebing Tinggi City. In the learning management process in this classroom organization the teacher has an important role for the implementation of teaching and learning in the classroom. The duties of teachers in learning include as educators and teachers, as mediators or learning resources, and facilitators, as models and role models, as motivators, as mentors and evaluators. Teachers must understand and understand their students better in learning. The research method used is a qualitative research method. The process of collecting data in this study used direct interviews with resource persons as teachers as well as homeroom teachers at SMA IT Kota Tebing Tinggi. From the results of the study, it was found that teachers experienced several obstacles due to the current state of the pandemic. What used to be able to learn effectively and efficiently was disrupted and the curriculum was also changed a lot.